Modelling Of Malaysian Reference Networks For Photovoltaic And Battery Energy Storage Systems Integration Studies - Mohammed, Hayder Salah (2021)
The thesis aims to develop and model six optimal Malaysian Medium Voltage (MV) Reference Networks (RNs) for the investigation of network performance under various future development scenarios. These include the integration of Photovoltaic (PV) system and Battery Energy Storage System (BESS) into the six MV RNs. The integration of PV system into the Malaysian MV distribution network is seen as one of the promising options to reduce carbon footprints for a low-carbon future. However, the integration of PV system into the existing MV distribution networks could cause reverse power flow problem. This reverse power flow may result in the increase of total network losses, voltage rise, and thermal violation of network components. Hence, one of the objectives of this thesis is to quantify the impact of PV integration with different PV locations, PV variability profiles, time resolution of PV profiles, and PV penetration levels on the optimal Malaysian MV RNs. In addition, the integration of PV system comes with other challenges such as PV output fluctuation, mismatch between PV generation and load demand, and network overvoltage. These issues will affect the power quality and the performance of the Malaysian MV distribution network. Therefore, this thesis also aims to identify the possible applications of BESS that could be used together with PV system to mitigate the potential network issues. The results on the optimal MV RNs show that the RNs with 11kV feeders have lower network losses as compared to the RNs with 33 and 11kV feeders. In addition, the losses in the rural RNs are higher than the urban and sub-urban RNs. The results also show that the utilization of optimal cables and transformers can reduce the network losses of between 3.52% to 19.22%. This translates into the increase of profit to the utility company of between RM 29 to RM 59884 per annum for the six RNs. Furthermore, the findings suggest that the total network losses are reduced between 3 to 7 times when the PV system is located at the end of 11kV feeder for the six RNs. The simulation results for PV variability study show that rural RNs with longer feeder need the highest number of voltage step changes (around 7300 annually) to maintain the voltage magnitude within the acceptable range. In addition, the time resolution case study suggests that one-minute interval PV generation profile is the most appropriate time resolution that could be used to analyze the MV total network losses for the urban, sub-urban, and rural RNs. The findings also emphasized the fact that once the PV penetration level threshold was achieved, the total network losses, voltage rise, and thermal violation of transformers will begin to increase. Finally, the BESS simulation results show the ability of lithium-ion BESS models to reduce the network maximum demand of between 4.84% to 52.71%. The BESS also helps to mitigate the issues which are caused by PV system integration through power output smoothening, demand following, and alleviating overvoltage problem.